2011
DOI: 10.1055/s-0031-1296748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascorbic Acid on Ambulatory Blood Pressure in Elderly Patients with Refractory Hypertension

Abstract: The increased production of reactive oxygen species plays a role in the etiology of hypertension, but the effects of antioxidants on blood pressure are controversial. However, antioxidants possibly lower blood pressure in elderly patients with hypertension, because vascular aging is also closely related to oxidative stress. Effects of chronic treatment with ascorbic acid (CAS 50-81-7; 600 mg/day for 6 months) on blood pressure and levels of C-reactive protein, 8-isoprostane, and malondialdehyde-modified low-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 12 publications
1
26
0
1
Order By: Relevance
“…Additionally, Sato and colleagues demonstrated a statistically significant reduction in SBP in elderly patients (65 years and older) with drug refractory hypertension compared with younger adults (younger than 65 years) who failed to show a significant BP reduction. After receiving 200 mg of ascorbic acid 3 times daily for 6 months, the mean 24‐hour ambulatory SBP decreased by approximately 20 mm Hg 24 . These findings are of interest, although the limited data prevents global recommendations on the efficacy of vitamin C in the treatment of hypertension.…”
Section: Agents With Possible Benefit In Hypertensionmentioning
confidence: 92%
“…Additionally, Sato and colleagues demonstrated a statistically significant reduction in SBP in elderly patients (65 years and older) with drug refractory hypertension compared with younger adults (younger than 65 years) who failed to show a significant BP reduction. After receiving 200 mg of ascorbic acid 3 times daily for 6 months, the mean 24‐hour ambulatory SBP decreased by approximately 20 mm Hg 24 . These findings are of interest, although the limited data prevents global recommendations on the efficacy of vitamin C in the treatment of hypertension.…”
Section: Agents With Possible Benefit In Hypertensionmentioning
confidence: 92%
“…In elderly patients with refractory hypertension already on maximum pharmacologic therapy, 600 mg of vitamin C daily lowered the BP by 20 ± 8/16 ± 5 mmHg [47].…”
Section: Vitaminsmentioning
confidence: 95%
“…A serum level of 100 μmol/L is recommended [1,70,71] . The SBP and 24 ABM show the most significant reductions with chronic oral administration of Vitamin C [200][201][202][203][204][205] . Block et al [206] in an elegant depletion-repletion study of vitamin C demonstrated an inverse correlation of plasma ascorbate levels, SBP and DBP.…”
Section: Fibermentioning
confidence: 95%
“…Dietary intake of vitamin C and plasma ascorbate concentration in humans is inversely correlated to SBP, DBP and heart rate [196][197][198][199][200][201][202][203][204][205][206][207][208][209][210] . An evaluation of published clinical trials indicate that vitamin C dosing at 250 mg twice daily will significantly lower SBP 5-7 mmHg and diastolic BP 2-4 mmHg over 8 wk [196][197][198][199][200][201][202][203][204][205][206][207][208][209][210] . Vitamin C will induce a sodium water diuresis, improve arterial compliance, improve endothelial function, increase nitric oxide and PGI2, decrease adrenal steroid production, improve sympathovagal balance, increase RBC Na/K ATPase, increase SOD, improve aortic elasticity and compliance, improve flow mediated vasodilation, decrease pulse wave velocity and augmentation index, increase cyclic GMP, activate potassium channels, reduce cytosolic calcium and reduce serum aldehydes [208] .…”
Section: Fibermentioning
confidence: 99%
See 1 more Smart Citation